2019
DOI: 10.3389/fphys.2019.01075
|View full text |Cite
|
Sign up to set email alerts
|

The Magnitude of Diving Bradycardia During Apnea at Low-Altitude Reveals Tolerance to High Altitude Hypoxia

Abstract: Acute mountain sickness (AMS) is a potentially life-threatening illness that may develop during exposure to hypoxia at high altitude (HA). Susceptibility to AMS is highly individual, and the ability to predict it is limited. Apneic diving also induces hypoxia, and we aimed to investigate whether protective physiological responses, i.e., the cardiovascular diving response and spleen contraction, induced during apnea at low-altitude could predict individual susceptibility to AMS. Eighteen participants (eight fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 36 publications
7
30
1
Order By: Relevance
“…However, the similar spleen contraction between SH and SL may indicate that some adaptation persists as a genetic predisposition to hypoxia tolerance in lowland Sherpa. Despite this, we found an overall association between resting spleen volume and spleen contraction, which has also been reported previously (Holmström et al, 2019).…”
Section: Figure 5 | (A)supporting
confidence: 81%
See 3 more Smart Citations
“…However, the similar spleen contraction between SH and SL may indicate that some adaptation persists as a genetic predisposition to hypoxia tolerance in lowland Sherpa. Despite this, we found an overall association between resting spleen volume and spleen contraction, which has also been reported previously (Holmström et al, 2019).…”
Section: Figure 5 | (A)supporting
confidence: 81%
“…It could therefore be speculated that HA dwellers could benefit from a similar cardiovascular priority system, temporarily directing blood flow to vulnerable tissues during severe hypoxic stress (e.g., during work at HA). In line with this, it was recently found that the diving response, initiated by apnea at low altitude, was negatively associated with AMS symptoms and maintained SpO 2 at HA in non-acclimatized lowlanders (Holmström et al, 2019). Why then would the HA-tolerant Sherpa have a less developed diving response than lowlanders?…”
Section: Figure 5 | (A)mentioning
confidence: 79%
See 2 more Smart Citations
“…By necessity, a field study like this has restrictions on which laboratory equipment can be used, and has to rely on smaller monitors and often simpler methods than in a stationary laboratory, as all equipment has to be carried on the back to location, and the laboratory has to be rapidly mounted before tests can begin at every location. The data from the equipment in this study have, however, been compared to results obtained with more advanced monitors in stationary laboratories at high altitude (e.g., Holmström et al 2019) and been found to be in agreement.…”
Section: Study Limitationsmentioning
confidence: 63%